Edge type effect in the gasification mechanism of graphene clusters with H2O and/or CO2: armchair vs. zigzag - Oyarzún Aravena, Andrea María; Gottschalk-Ojeda, Catalina; Moya-Barria, Ivan; Vallejos-Burgos, Fernando (My University, 2022)
Reactions of carbon and oxygen containing molecules, such as O-2, NO, H2O and CO2, are ubiquitous on earth and the universe. Through ab initio calculations, we study the reactions of H2O and CO(2)with small graphene clusters containing armchair edges, both H- and non-H terminated, and compare with studies of zigzag carbon edges interacting with oxygen-containing molecules. Our results highlight the differences between armchair and zigzag sites and our mechanistic comparisons regarding carbon reactions with H2O and CO2, identify similarities and differences on their reactivity. In the case of H2O, adsorption is favored over armchair sites exhibiting no rotational process and the H-2 desorption step is favored over zigzag sites. Regarding the CO2 reaction, chemisorption is favored on zigzag sites. Several adsorption mechanisms lead to the formation of lactone groups as the most stable structures. A specific armchair CO desorption path for stable functional groups exists, agreeing with experimental reports, and thus completing our explanations for this reaction, previously limited to zigzag sites. Finally, the reaction over armchair sites leads to direct formation of pentagonal rings, without an active site deactivation process and with low activation energies. This deeper understanding provides further possibilities for improving the control of carbon-oxygen reactions.
Keywords: Zigzag; Chemisorption; Carbon fibers